ANALISIS SPESIES LOGAM Fe(II), Fe(III), Cr(III) DAN Cr(VI) DALAM LIMBAH CAIR INDUSTRI MENGGUNAKAN METODE KOMBINASI SPEKTROFOTOMETRI UV-TAMPAK DAN SPEKTROFOTOMETRI SERAPAN ATOM (AAS) - MUSTANGINAH, TITIN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
Iron(II), iron(III), chromium(VI) and chromiumr(III) in industrial waste water were determined using combination of UV-Visible spectrophotometry and atomic absorption spectrophotometry (AAS). Species of iron(II) was analyzed as its 1,10- phenantroline complex and Cr(VI) as its 1,5-diphenylcarbazide complex, whereas species of Fe(III) and Cr(VI) were calculated indirectly by the difference after analyzing the total Fe and Cr by AAS. For the determination of Fe(II) and Cr(VI) species using a spectrophotometer UV?Visible, the optimum conditions of analysis were first investigated. The optimum experimental conditions obtained were then applied for the analysis of Fe(II) and Cr(VI) in some industrial waste water samples using calibration curve techniques. For the analysis of total Fe and Cr, AAS was used. Finally, from these results of the two methods the concentration of Fe(III) and Cr(VI) were estimated by subtracting the concentration of species Fe(II) and Cr(VI) from the total concentration of Fe and Cr, respectively.From the study, it was obtained that optimum conditions for determining the species Fe(II) is at maximum wavelength of 510 nm, stability time up to 450 min, mole ratio of ligand to Fe = 7:1 and pH ? 6. For Cr(VI)-DPC complex it was found that ?max = 540 nm, stability time from 5–60 min, mole ratio of Cr(VI): ligand = 1:43 and pH ? 2.0. The metal speciation analysis results indicated that the concentration of Fe(II) in tannery waste water was 0.16–0.26 ppm, in metal plating wastes was 8.88 ppm, in textile wastes = 0.09–0.25 ppm, in Piyungan IPAL TPA waste water 0.09?4.26 ppm and in batik waste water 0.00–1.05 ppm. Species of Cr(VI) in tannery waste water was found to be 0.00?0.16 ppm, metal plating was 1427.4 ppm, textile waste was 0.01–0.03 ppm, the Piyungan IPAL TPA was 0.00–0.15 ppm and batik wastes was 0.00–0.02 ppm. The calculation result of Fe(III) species in tannery waste water was 0.07–0.26 ppm, in waste metal plating was 18.17 ppm, in textile was 0.09–0.521 ppm, in Piyungan IPAL TPA wastes was 0.03–2.35 ppm and in batik waste was 0.01–0.50 ppm. As for Cr(III) species in tannery waste water, it was found to be 0.00–1.88 ppm, in metal plating was 277.66 ppm, in textile 0.01–0.03 ppm, in Piyungan IPAL TPA 0.02–0.11 ppm and in batik 0.01–0.02 ppm. The results showed that UV-Visible spectrophotometric method in combination with AAS can be used for metal speciation analysis of Fe and Cr in environmental samples. ABSTRAKTelah dilakukan analisis spesies Fe(II), Fe(III) dan Cr(VI), Cr(III) dalam limbah cair industri menggunakan metode kombinasi spektrofotometri UV?tampak dan spektrofotometri serapan atom (AAS). Analisis spesies Fe(II) menggunakan ligan 1,10-fenantrolin dan Cr(VI) menggunakan ligan 1,5?difenilkarbazid sebagai pengompleks, spesies Fe(III) dan Cr(III) ditentukan secara tidak langsung dari selisih Fe dan Cr total dengan Fe(II) dan Cr(VI). Penentuan spesies Fe(II), Cr(VI) menggunakan spektrofotometer UV-tampak diawali dengan penentuan kondisi optimum analisis. Kondisi optimum percobaan yang diperoleh diaplikasikan dalam analisis spesies Fe(II) dan Cr(VI) dalam beberapa sampel limbah cair industri dengan teknik kurva kalibrasi. Metode AAS untuk menganalisis Fe total dan Cr total. Kemudian dari hasil tersebut berturut-turut dihitung selisih konsentrasi spesies Fe(II) dan Cr(VI) dengan Fe dan Cr total sehingga diperoleh konsentrasi spesies Fe(III) dan Cr(III). Kondisi optimum penentuan spesies Fe(II) adalah panjang gelombang maksimum 510 nm, waktu kestabilan sampai 450 menit, rasio mol ligan:Fe(II) = 7:1 dan pH larutan ? 6,0. Untuk kompleks Cr(VI)-DPC panjang gelombang maksimum 540 nm, waktu stabil kompleks dimulai menit ke-5 sampai ke-60, rasio mol Cr(VI):ligan = 1:43 dan pH larutan ? 2,0. Hasil spesiasi logam menunjukkan spesies Fe(II) dalam limbah cair industri penyamakan kulit sebesar 0,16–0,26 ppm, limbah pelapisan logam 8,88 ppm, limbah tekstil 0,09–0,25 ppm, limbah IPAL TPA Piyungan 0,09?4,26 ppm, limbah batik 0,00–1,05 ppm. Spesies Cr(VI) dalam limbah cair industri penyamakan kulit 0,00?0,16 ppm, limbah pelapisan logam 1427,40 ppm, limbah tekstil 0,01?0,03 ppm, limbah IPAL TPA Piyungan 0,00–0,15 ppm, limbah batik 0,00?0,02 ppm. Hasil penentuan spesies Fe(III) dalam limbah cair industri penyamakan kulit adalah 0,07–0,26 ppm, limbah pelapisan logam 18,17 ppm, limbah tekstil 0,09–0,52 ppm, limbah IPAL TPA Piyungan 0,03–2,35 ppm, limbah batik 0,01–0,50 ppm. Adapun untuk spesies Cr(III) dalam limbah cair industri penyamakan kulit diperoleh kadar 0,00–1,88 ppm, limbah pelapisan logam 277,66 ppm, limbah tekstil 0,01–0,03 ppm, limbah IPAL TPA Piyungan 0,02–0,11 ppm, limbah batik 0,01–0,02 ppm. Hasil penelitian menunjukkan bahwa metode spektrofotometri UV-tampak yang dikombinasikan dengan AAS dapat digunakan untuk analisis spesiasi logam Fe dan Cr dalam sampel lingkungan.